2001
DOI: 10.1073/pnas.041619198
|View full text |Cite
|
Sign up to set email alerts
|

Zinc metallothionein imported into liver mitochondria modulates respiration

Abstract: Metallothionein (MT) localizes in the intermembrane space of liver mitochondria as well as in the cytosol and nucleus. Incubation of intact liver mitochondria with physiological, micromolar concentrations of MT leads to the import of MT into the mitochondria where it inhibits respiration. This activity is caused by the Nterminal ␤-domain of MT; in this system, the isolated C-terminal ␣-domain is inactive. Free zinc inhibits respiration at concentrations commensurate with the zinc content of either MT or the is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
170
1
2

Year Published

2001
2001
2017
2017

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 237 publications
(178 citation statements)
references
References 63 publications
4
170
1
2
Order By: Relevance
“…Hunter and Ford (1955) first reported that micro-molar levels of free zinc ions dramatically inhibited coupled liver mitochondrial oxygen consumption stimulated by β-hydroxybutyrate. Similar inhibitory effects of zinc were obtained by Ye et al (2001) with uncoupled liver mitochondria. Skulachev et al (1967) found that μM free zinc ions inhibited electron transfer between cytochrome b and c 1 of complex III and had no effect on the cytochrome c oxidase; and our results are in general agreement with those observations.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Hunter and Ford (1955) first reported that micro-molar levels of free zinc ions dramatically inhibited coupled liver mitochondrial oxygen consumption stimulated by β-hydroxybutyrate. Similar inhibitory effects of zinc were obtained by Ye et al (2001) with uncoupled liver mitochondria. Skulachev et al (1967) found that μM free zinc ions inhibited electron transfer between cytochrome b and c 1 of complex III and had no effect on the cytochrome c oxidase; and our results are in general agreement with those observations.…”
Section: Discussionsupporting
confidence: 78%
“…We have reported that metallothionein is an effective chaperone for the delivery of zinc to the mitochondrial inner membrane for direct exchange with zinc uptake transporter, so it is likely that this relationship is applicable to zinc inhibition in liver cells. This was suggested by Ye et al (2001) who found that zinc-metallothionein entered the mitochondrial intermembrane space where it inhibited the respiration of liver mitochondria. They showed that, in the absence of a significant free Zn + + pool, zinc could be transferred from metallothionein to zinc-acceptor site; and that localized oxidation of zinc-metallothionein would enhance the effect by facilitating its release of zinc.…”
Section: Discussionmentioning
confidence: 86%
“…Once delivered to the intermembranous space, the ZnLigand could be exposed to conditions (such as oxidative environment; pH change) that facilitate the release of zinc from the ligand; thereby providing a localized pool of free Zn + + as the reactive form of zinc. This possibility was proposed for the effects of zinc metallothionein (ZnMT) on terminal oxidation of liver mitochondria (Maret, 1994;Ye et al, 2001). Alternatively or additionally, the ZnLigand can donate its zinc to a recipient molecule by a direct transfer that does not involve free Zn + + ions as an intermediary (Halthout et al, 2001).…”
Section: Zinc Trafficking Into Mitochondriamentioning
confidence: 99%
“…MT could translocate into another cellular compartment in which the environment is more oxidizing. Indeed, MT is now known to be a constituent of the intermembrane space of liver mitochondria [27]. Generating a transient reactive oxidizing species could also change the redox environment.…”
Section: Biological Considerations: Triggering Zinc Release and Bindimentioning
confidence: 99%